Study on Mechanical Properties of Basalt Fiber-Reinforced Concrete with High Content of Stone Powder at High Temperatures - Lina Xu; Daohan Song; Ning Liu; Wei Tian (Advances in Materials Science and Engineering)
Concrete materials are an important part of global structure, and their fire resistance directly affects the safety of buildings and tunnels. In this study, basalt fiber was used to reinforce concrete with high content of stone powder in order to enhance its high-temperature performance. The mechanical properties and ultrasonic characteristics at different temperatures were studied using the cube compressive strength test and nonlinear ultrasonic test. The results indicated that the addition of basalt fiber in specimens improved their compressive strength; however, this strength did not continuously increase with increases in the fiber length and fiber content, and the optimal values for fiber length and fiber content were determined to be 12 mm and 1 kg/m3 at 600°C, respectively. With increases in temperature, the unconfined compressive strength increased first and then decreased. When the temperature was 400°C, the unconfined compressive strength of the specimens reached their highest values and then decreased. When the temperature was 400°C and 600°C, the strength of the stone powder concrete with fiber was higher than that without fiber, which shows that fiber can improve the mechanical properties of concrete at high temperatures. Based on the Box-Behnken design (BBD) method, the unconfined compressive strength response regression model of basalt fiber-reinforced concrete with high content of stone powder, which follows parameters including fiber content, fiber length, and temperature at high-temperature environments, was established, and it was found that the interaction of fiber content, fiber length, and the temperature was significant based on multifactor interaction analysis. The analysis of ultrasonic signals based on the S transform showed that, with increases in temperature, the amplitudes of the acoustic response signals, the corresponding frequency spectrum, and the time-frequency spectrum were clearly reduced. At the same temperature, the amplitudes of the acoustic response signals of different concrete testing blocks did not change much and remained at the same level.